Dairy marketing in Ethiopia: Markets of first sale and producers' marketing patterns - Debrah, S.K.; Anteneh, B. (International Livestock Centre for Africa, 1991)
This study is part of a larger study on dairy marketing in Ethiopia, and concentrates on the producers'end of the marketing chain. Specifically, the markets of first sale used by dairy producers were identified and the marketing patterns of three categories of dairy producers (intra-urban, peri-urban and peasant) were investigated. The study was carried out on a sample of 173 dairy producers between February and July 1986, using structured questionnaires. Fresh-milk sales averaged between 0.5 and 6 litres per lactating cow per day, with intra-urban and peri-urban producers specialising in fresh-milk sales. Most of the fresh milk was sold to catering and government institutions in Addis Ababa from which net profits of EB 0.63 and EB 0.66/litre, respectively, were obtained. Peasant producers sold milk, butter and cheese, as specialised enterprise milk collection centre sold more milk and less butter and cheese than those far away. High net profits was identified as an important motive guiding the choice of sales outlet.